Marine control technology - Majunder, J.; Fernandez, Elstan A. (Shroff Publishers & Distributors Pvt.Ltd, 2014)
The shipping industry has been growing in leaps and bounds over the past few decades. The answer to reduced manning, together with demanding operating schedules, has more often than not been automation. Hence the need of the hour for a seafarer is adequate knowledge of UMS environments and their supporting systems onboard ships. With almost 30 years of first-hand experience by each of us in this mammoth industry, we have seen the evolution from control elements and systems of the post 2nd world-war era to the most sophisticated components and networks available today. It has indeed been a wonderful journey through time!